Drivers of obesity : associations of physical activity, sedentary behaviour and diet on metabolic health and the gut microbiota : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Tāmaki Makaurau, Aotearoa New Zealand - Slater, Joanne (Massey University, 2023)
Background: Regular physical activity (PA) and limited time spent sedentary are important for almost all aspects of health, including prevention and treatment of obesity. Aim: To describe the PA and sedentary behaviour (SB) of healthy, lean and obese, Pacific and NZE women, aged 18-45 years; and to explore the associations of PA and SB with diet, BF%, biomarkers of metabolic health, and gut microbiota composition. Methods: Pacific (n = 142) or NZE (n = 162) women aged 18–45 years with a self- reported body mass index of either 18.5–25.0 kg/m2 or ≥30.0 kg/m2 were recruited. Whole body dual-energy X-ray absorptiometry was used to subsequently stratify participants as either low (<35%) or high (≥35%) BF%. Eight-day accelerometery assessed PA and SB levels. Meeting the PA guidelines was defined as accumulation of ≥ 30 minutes of moderate or greater intensity activity on ≥ 5 days per week OR 150 minutes of moderate to vigorous PA (MVPA) per week. Dietary intake was assessed using a 5-day food record. Fasting blood was analysed for biomarkers of metabolic health, and whole body dual-energy X-ray absorptiometry was used to estimate body composition. Bulk DNA was extracted from faecal samples and the metagenomic sequences associated with the microbiota were analysed using MetaPhlAN and QIIME2 software. Adjusted multivariate regression models were conducted to explore the associations between PA, SB and diet, body composition and biomarkers of metabolic health, and between PA, SB and gut microbiota composition. Results: Less than half Pacific women were meeting the PA guidelines (high-BF%; 39% and low-BF%; 47%) versus 81% of low-BF% and 65% of high-BF% NZE women. Low-BF% Pacific women were more sedentary than all other women (p<0.05): Pacific low- 10.4 and high-BF% 9.93 and NZE low- 9.69 and high-BF% 9.96 hours/day. Every additional 10-minutes spent in MVPA was associated with 0.9% lower total and trunk fat and 0.7% lower gynoid fat in all women (p<0.05). Among Pacific women; every 100 cpm increase in total PA was associated with 6% lower fasting plasma insulin. Every 10-minute increase in MVPA was associated with 8% lower fasting plasma insulin in both ethnic groups (p<0.05). Among NZE women, every one-hour increase in sedentary time was associated with 0.8% higher gynoid fat (p<0.05), and longer weighted median sedentary bout length was associated with higher BF% (gynoid fat 0.3%, total body 0.4%, trunk 0.4%, android 0.4% and visceral fat 0.4% (p<0.05)) and 14% higher C-reactive protein (CRP) (p<0.05). No associations between SB and body composition or metabolic markers were found among Pacific women. There was no significant difference in average total energy intake between Pacific and NZE women or BF% groups. No women were consuming more than the carbohydrate AMDR (>65% total energy). Pacific women’s mean daily starch intake was significantly higher than NZE women (g/day, and % total energy intake). Only the NZE low-BF% groups mean fibre intake was above the recommended daily intake of ≥25g/day. All the women that were in the lowest quartile of fibre intake, and particularly the NZE women, had a lower odds of meeting the PA guidelines (OR 0.72 (p=0.008) and OR 0.66 (p=0.021) respectively) compared to women in the top three quartiles of fibre intake. All the women that were in the lowest quartile of polyunsaturated fat intake, especially Pacific women had a lower odds of meeting the PA guidelines compared women in the top three quartiles (0.76, p=0.027 and OR 0.67, p=0.030 respectively). Among NZE women, every one SD increase in total PA (197 cpm/day) was associated with 36.3% higher relative abundance of Erysipelotrichaceae (p=0.031) and 37.9% lower relative abundance of Verrucomicrobiaceae (p=0.029). Every one SD increase in SB (1.45 hours/day) was associated with a 28% lower relative abundance of Erysipelotrichaceae (p=0.030). Every one SD increase in NZE women’s total PA was associated with 23.1% higher Firmicutes:Bacteroidetes ratio (p=0.031), whereas among Pacific women, every 1 SD increase in MVPA was associated with 22.8% lower (p=0.034) Firmicutes:Bacteroidetes ratio. Conclusion: Increased time spent in PA of all intensities and breaking-up prolonged SB was associated with healthier body composition and lower metabolic disease risk in Pacific and NZE women. Compared to NZE, the impact of increased total PA on fasting insulin may be greater in Pacific women and inflammation may be a pathway through which SB impacts cardiovascular risk, especially for NZE women. Although higher total PA and lower SB was associated with some aspects of the gut microbiota composition, more needs to be known about the mechanisms driving associations between PA SB and the gut microbiota to enable these findings to be interpreted.
Keywords: Body composition; Exercise; Health aspects; Food habits; Gastrointestinal system; Microbiology; Women; Health and hygiene; New Zealand; 321004 Nutritional science